2002
DOI: 10.1002/ar.10090
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of the buccinator muscle in cat (Felis domestica)

Abstract: Published descriptions of the buccinator muscle of the cat (Felis domestica) differ from those for the same muscle in other mammals. Only an oral component of the muscle has been described in cats, not a buccal part. The purpose of this study was to identify the buccinator muscle in the cat and report on its anatomical features in detail. Dissections of the facial muscles were carried out on 12 specimens of adult cats (6 males and 6 females) that had been fixed with 10% formalin. We then observed the facial mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…An infraauricular incision was made, and the trunk of the extratemporal facial nerve was identified as it exits the temporal bone by the external auditory canal. The dense epineurium was penetrated with a 30‐gauge needle, and the array was introduced into the facial nerve proximal to the bifurcation into the dorsal and ventral rami with the aid of a micropositioner and with the goal of inserting all 16 stimulating sites in neural tissue. The site and angle of insertion were not programmed or pre‐determined; positioning of the array was dictated by the surgical anatomy and access to the nerve with the micropositioner.…”
Section: Methodsmentioning
confidence: 99%
“…An infraauricular incision was made, and the trunk of the extratemporal facial nerve was identified as it exits the temporal bone by the external auditory canal. The dense epineurium was penetrated with a 30‐gauge needle, and the array was introduced into the facial nerve proximal to the bifurcation into the dorsal and ventral rami with the aid of a micropositioner and with the goal of inserting all 16 stimulating sites in neural tissue. The site and angle of insertion were not programmed or pre‐determined; positioning of the array was dictated by the surgical anatomy and access to the nerve with the micropositioner.…”
Section: Methodsmentioning
confidence: 99%
“…Original dissections of the facial muscles have been carried out in some cases (e.g. Vick et al, 2007;Waller et al, 2013), but due to the extensive literature available on the facial musculature of the domestic cat (Mivart, 1881;Reighard and Jennings, 1901;Davidson, 1927;Crouch, 1969;Done et al, 1996;Tomo et al, 2002), this was deemed unnecessary. Second, the form and location of muscles were matched to observed facial movements by analysing frame-by-frame spontaneous facial behaviour from video footage.…”
Section: Study 1: Development Of Catfacsmentioning
confidence: 99%
“…In cats, the muscles are absent and the consequent movement of pushing the lips towards the midline has very different appearance changes. The buccinator muscle has been described as responsible for pushing the lips medially and keeping food inside the mouth, during mastication (Tomo et al, 2002). Since no puckering of the lips is seen in cats and there are different muscles acting, this movement is coded in cats as AU118 and the same designation is maintained.…”
Section: Au118-lip Puckermentioning
confidence: 99%
“…The zygomatic branch of the n.facialis was reported to give off branches to not only the cheek muscles but also to both eyelids (Tomo et al., 2002). In our study, it was observed that the buccal branch and the zygomatic branches gave off branches to the cheek muscles and the orbicular muscles around the eyes, respectively.…”
Section: Discussionmentioning
confidence: 99%